2019
DOI: 10.1007/s00330-018-5973-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific association of body composition with inflammatory and adipose-related markers in healthy elderly Europeans from the NU-AGE study

Abstract: Objectives The aim of this work was to examine the cross-sectional relationship between body composition (BC) markers for adipose and lean tissue and bone mass, and a wide range of specific inflammatory and adipose-related markers in healthy elderly Europeans. Methods A whole-body dual-energy X-ray absorptiometry (DXA) scan was made in 1121 healthy (65–79 years) women and men from five European countries of the “New dietary strategies addressing the specific needs of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 59 publications
0
40
0
2
Order By: Relevance
“…Similarly, visceral adiposity determined by CT was shown to be correlated with an increased risk in men over 50 years old (111,139). A recent analysis investigating the relationship between BC and inflammation in a large European cohort of elderly has shown that BC and regional lean/fat distribution can define BC clusters that differently associate with inflammatory markers and inflammatory profiles (29).…”
Section: Associations Of Fat Mass With Mobility Disability and Mortmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, visceral adiposity determined by CT was shown to be correlated with an increased risk in men over 50 years old (111,139). A recent analysis investigating the relationship between BC and inflammation in a large European cohort of elderly has shown that BC and regional lean/fat distribution can define BC clusters that differently associate with inflammatory markers and inflammatory profiles (29).…”
Section: Associations Of Fat Mass With Mobility Disability and Mortmentioning
confidence: 92%
“…Within the framework of the European NU-AGE project (conducted from 2011 to 2016) a DXA scan has been carried out in a large number (N = 1,121) of sex-balanced, free-living, apparently healthy older adults aged 65-79 years enrolled in 5 European countries (Italy, France, United Kingdom, Netherlands and Poland) (28) for the first time. The results showed that BC characteristics are different in elderly women and men across Europe (19) and that a better adipose-related inflammatory profile is associated to a more favorable BC in terms of fat and lean mass markers (29). In this review, we summarize the present knowledge of available imaging methods to measure BC, with a focus on the measurement of BC changes occurring with age and we discuss pros and cons of each technique.…”
Section: Introductionmentioning
confidence: 99%
“…Height and weight were measured using standardised procedures and body composition was assessed using whole body Dual energy X-ray absorptiometry (DXA) as described elsewhere [32]. DXA scans were performed by trained technicians according to state-of-the-art technique and manufacturer recommendations.…”
Section: Assessment Of Body Compositionmentioning
confidence: 99%
“…Total and regional fat and lean masses were derived. Skeletal muscle mass index (SMI, %) was derived as previously described [32][33][34]: (appendicular lean mass (kg)/total body weight (kg)) × 100.…”
Section: Assessment Of Body Compositionmentioning
confidence: 99%
“…A comprehensive clinical and molecular characterization was performed at baseline and after the 1-year intervention, and results achieved so far in the framework of this study have demonstrated a beneficial effect of the Mediterranean-like diet on global cognition and episodic memory (Marseglia et al 2018), osteoporosis , immune function (Maijo et al 2018), and cardiovascular health , as well as on the proteasomal proteolysis (Athanasopoulou et al 2018). The NU-AGE study design (different countries with different dietary traditions and habits) and the large number of collected data allowed to evaluate the impact of relevant variables usually poorly investigated (age, sex, and ethnicity/genetics, as well as individual characteristics) on different parameters at baseline and after the intervention (Konz et al 2018;Marseglia et al 2018;Ostan et al 2018;Pujos-Guillot et al 2018;Santoro et al 2018Santoro et al , 2019Jennings et al 2019). Importantly, the enrolled subjects were recruited also in non-Mediterranean countries (Poland, the Netherlands, and the UK).…”
Section: Introductionmentioning
confidence: 99%